The new law school : reexamining goals, organization and methods for a changing world / Daniela Ikawa, Leah Wortham (eds.). - Ikawa, Daniela; Wortham, Leah (Jagiellonian University Press, 2010)
This collection of essays is a unique contribution to understanding the issues confronting law schools in Central and Eastern Europe and countries of the former Soviet Union as they seek to ensure that their programs meet the needs of 21st century lawyers. The book is unusual in two ways. First, most of the authors are faculty members at universities in the region. Despite a plethora of initiatives to reform legal education in Central and Eastern Europe and countries of the former Soviet Union, there has been little literature on the topic coming from the region itself. Second, the essays address structural issues as well as pedagogical ones (e.g., the disincentives for academics to invest time in developing new teaching methodologies and the problems posed by rigid government standards for higher education). It is particularly useful to have these essays collected in one book, so that readers can see both problems and some suggested solutions in a cross-cultural context.